Bundling strategy to simultaneously improve the mechanical strength and oxygen permeation flux of the individual perovskite hollow fiber membranes - An, R.; Song, J.; Li, Y.; Tan, X.; Sunarso, J.; Zhang, C.; Wang, Shaobin; Liu, Shaomin (Elsevier BV, 2017)
A single chopstick can be broken easily while a tightly bundled collection of them can withstand much more mechanical stress. This is the case for the individual perovskite hollow fiber membranes for air separation where their inherently low mechanical strength limits their application. Here, several La0.6Sr0.4Co0.2Fe0.8O3-d hollow fibers have been bonded together to form a bundle, significantly improving the mechanical properties and the oxygen flux. The strategy for such improvement is the application of porous Ba0.5Sr0.5Co0.4Fe0.6O3-d perovskite as the binder. The perovskite binder not only plays the function of binding to increase the mechanical strength but also works as the catalyst attached on the exterior of the hollow fiber to improve the oxygen reduction surface reactions, thus leading to the higher oxygen flux.